STRUKTUR DAN KOMPOSISI JENIS VEGETASI DI HUTAN SEKUNDER: STUDI KASUS KHDTK LABANAN PROVINSI KALIMANTAN TIMUR (Structure And Species Composition Of Tree In Secondary Forest: A case study at KHDTK Labanan, East Borneo Province) - Karmilasanti Karmilasanti; M. Fajri (Pusat Penelitian dan Pengembangan Hutan, 2020)
ABSTRACT Unproductive forests in the form of secondary forest tend to be converted into forest plantation, agriculture and other land uses. Even though the secondary forest can still be restored using native commercial species. This study aimed to determine the structure and composition of stands, the potential of residual stands, and natural regeneration of the secondary forest in KHDTK Labanan. The research was carried out through vegetation inventory and vegetation analysis to calculate stand potential, natural regeneration, Importance Value Index (IVI), and species diversity. The results showed the structure of commercial species stands in secondary forests in the Labanan KHDTK followed an inverted